Pengaruh Kompensasi dan Pengembangan Karir terhadap Kinerja Karyawan - Margono, Pramono (Journal of Economics & Business UBS, 2020)
In the globalization era, human capital readiness is a must. Since people is an asset of the company. The objective of the company depend on the people competencies and called human capital readiness. Since the improvement of employee productivity is the critical pathÂ  to improved the company performance, Â the purpose of this research is to examine the influence of compesation and career development on employees performance . The first hypothesis examine wheter compensation influences performance. The second hypothesis examine wheter career development influences performance .The population in this researchare all employees at Company X Jakarta. This research uses by using technique of sampling. Data were collected using a survey method and analyzed with doubled linear regression. The result of hypothesis test shows that compensation has a simultaneous and partially to performance.Another result of this research show that career development has a simultaneons and partially to performance.